Algılanan Örgütsel Desteğin Çalışanların İşe Yabancılaşması ve İşten Ayrılma Niyetine Etkisi Üzerine Bir Araştırma - Tokmak, Mutlu (Muş Alparslan Üniversitesi, 2020)
The aim of this study is to determine the effect of perceived organizational support on work alienation and intention to quit. Descriptive statistical analysis, correlation and regression analyzes were performed in the study. As a result of the correlation analysis, a negative correlation between the perception of organizational support and alienation to work was determined as 0.432 percent. There was no significant relationship between perceived organizational support and turnover intentions. A positive and significant 0.674 moderate correlation was found between work alienation and intention to quit. As a result of linear regression analyzes, it was found that perceived organizational support had a negative effect of 0.187 on work alienation. Perceived organizational support has no statistically significant effect on turnover intentions. It was found that alienation had a positive effect of 0.454 on the turnover intentions.

Bu çalışmanın amacı, çalışanların algıladıkları örgütsel desteğin işe yabancılaşma ve işten ayrılma niyeti üzerine etkisinin belirlenmesidir. Araştırmada betimsel istatistik analizi, korelasyon ve regresyon analizleri gerçekleştirilmiştir. Korelâsyon analizleri neticesinde, örgütsel destek algısı ile işe yabancılaşma arasında negatif yönlü 0.432 oranında orta düzeyde ilişki tespit edilmiştir. Algılanan örgütsel destek ile işten ayrılma niyeti arasında anlamlı bir ilişki tespit edilememiştir. İşe yabancılaşma ile işten ayrılma niyeti arasında pozitif yönlü ve anlamlı 0.674 oranında orta düzeyde korelâsyon olduğu belirlenmiştir. Basit doğrusal regresyon analizleri neticesinde, algılanan örgütsel desteğin işe yabancılaşma üzerinde 0.187 oranında negatif etkisinin olduğu belirlenmiştir. Algılanan örgütsel desteğin işten ayrılma niyeti üzerinde istatistiksel olarak anlamlı bir etkisi saptanmamıştır. İşe yabancılaşmanın, işten ayrılma niyeti üzerinde ise 0.454 oranında pozitif etkisi olduğu tespit edilmiştir.
A Research on the Effects of Perceived Organizational Support on the Work Alienation and Turnover Intentions of Employees
anemon
Keywords: Organizational Support Perception; Work Alienation; Turnover Intentions; Algılanan Örgütsel Destek; İşe Yabancılaşma; İşten Ayrılma Niyeti